2016
DOI: 10.1177/1557988316655785
|View full text |Cite
|
Sign up to set email alerts
|

The Loss of Boystown and Transition to Online Sex Work: Strategies and Barriers to Increase Safety Among Men Sex Workers and Clients of Men

Abstract: Men sex workers in Vancouver have largely transitioned from street to online solicitation coinciding with losing “Boystown,” the main outdoor sex work stroll for men. This article explores strategies and barriers to increase safety among men and trans sex workers and clients of men in Vancouver, Canada. Qualitative interviews were conducted (2012–2013) with 61 self-identified men who currently buy and/or sell sex in a community-based research project known as CHAPS (Community Health Assessment of Men Who Purch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 36 publications
(83 reference statements)
1
69
0
Order By: Relevance
“…While the concerns around the implications of the move online to safety, risk and crimes experienced by sex workers has begun to emerge (Argento et al ), the connections between crimes, under‐reporting and safety strategies are questions that our research has addressed, filling the gaps noted by other scholars (Jones ).…”
Section: Shifting Trends: Crime Against Sex Workers and Risk Managementmentioning
confidence: 95%
See 3 more Smart Citations
“…While the concerns around the implications of the move online to safety, risk and crimes experienced by sex workers has begun to emerge (Argento et al ), the connections between crimes, under‐reporting and safety strategies are questions that our research has addressed, filling the gaps noted by other scholars (Jones ).…”
Section: Shifting Trends: Crime Against Sex Workers and Risk Managementmentioning
confidence: 95%
“…It has been established that sex workers develop a range of protective strategies (Harris, Nilan and Kirby ; Sanders ) and skills to manage and negotiate the risks involved in selling sexual services are part of the occupational culture (O’Neill ; Pitcher ). Beyond the Gaze research has found that at all stages of commercial sexual encounters negotiated or delivered online, particularly early interactions with clients, it is important that sex workers are enabled to put in place protective strategies (Ray ; Argento et al, ; Cunningham 2011). In our study, we asked sex workers if the internet was important for their safety and about the safety methods they employed.…”
Section: Safety Strategies Screening and Risk Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health-related benefits associated with Internet-based sex work, defined as the use of Internet by adults to facilitate consensual exchange of sexual services for money, include increased income, autonomy, and safety when compared with street-level sex work or working for a third party [1,4-6]. Internet-based sex workers can also, however, experience depression, isolation, violence, sexually transmitted infections (STIs), and substantial barriers in accessing and receiving health services [2,7-13].…”
Section: Introductionmentioning
confidence: 99%